Os sentidos e desafios da participação - Lígia Helena Hahn Lüchmann (Ciências Sociais Unisinos)
This article analyzes some challenges and difficulties of the participatory experiences in Brazil particularly of the Managing Councils and the Participatory Budgeting in constituting themselves as experiences of deliberative democracy. Having in mind the use and the widespread appeal to the idea of participation over the past years, the paper presents the different meanings of political participation, which is understood as a process of participation in the decision-making spaces of public policies. This widespread appeal to participation seems to hide crucial differences about the meanings of democracy. In the light of the theory of deliberative democracy and many studies that have been analyzing empirical experiences, some problems, limits and challenges of these experiences are presented here.